The Neurobiology, Physiology, and Psychology of Pain - Rajendram, Rajkumar; Rajendram, Rajkumar; Preedy, Victor R.; Patel, Vinood B. (Elsevier Science, 2021)
The Neurobiology, Physiology and Psychology of Pain focuses on bettering readers$1 (Bunderstanding of acute and chronic pain. Featuring chapters on neurotransmitters, pharmacology, and brain imaging, this volume discusses, in detail, the mechanisms of pain and experimental studies undertaken to better understand the pathways involved. The translational work in this area has applicability for neurologists, anesthesiologists, pharmacologists, and anyone working in the intersection of these areas. This volume is integral for anyone interested in the molecular underpinnings of pain at every level. Provides comprehensive coverage on a broad range of topics related to the neuroscience of pain Contains an abstract, key facts, a mini dictionary of terms, and summary points to aid in understanding in each chapter Features chapters on molecular pathways, imaging and a deep look at behavior associated with the experience of pain Contains unique topics that will help readers navigate key areas for research and further clinical recommendationss